2015
DOI: 10.1097/aci.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Difficult-to-control asthma

Abstract: Purpose of review The aim of the present review is to discuss the epidemiology of inadequate asthma control with an examination of contributing environmental factors. Recent findings Despite advances in asthma therapies, a proportion of patients with asthma continue to have difficulty gaining adequate asthma control. Asthma severity and control in childhood is of particular importance as it translates to asthma morbidity in adulthood. Children with comorbid severe allergic rhinitis were more likely to have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…A 20% increased length of hospital stay was also found in ETS-exposed asthmatic children [57]. ETS exposure also impacts on asthma control with decreased response to inhaled corticosteroids and impaired histone deacetylase-2 function, possibly contributing to steroid resistance in asthmatic children [58]. In utero tobacco smoke exposure increased age-related airway hyperresponsiveness and reduced the efficacy of inhaled corticosteroids in asthmatic children [59].…”
Section: Resultsmentioning
confidence: 99%
“…A 20% increased length of hospital stay was also found in ETS-exposed asthmatic children [57]. ETS exposure also impacts on asthma control with decreased response to inhaled corticosteroids and impaired histone deacetylase-2 function, possibly contributing to steroid resistance in asthmatic children [58]. In utero tobacco smoke exposure increased age-related airway hyperresponsiveness and reduced the efficacy of inhaled corticosteroids in asthmatic children [59].…”
Section: Resultsmentioning
confidence: 99%
“…Cockroaches produce several allergens that induce sensitization, and exposure to high levels of cockroach allergens at home is a major risk factor for symptoms in sensitized individuals [68]. Recent data suggest that cockroach allergen may be a most relevant urban allergen exposure and may be related to asthma severity [69]. Indoor allergen exposure in inner-city areas has been of particular interest given that patients living in urban areas have increased asthma severity, decreased asthma control, and greater health care use [70].…”
Section: Cockroach Allergens Sensitization and Severe Asthmamentioning
confidence: 99%
“…Ahluwalia et al observed that sensitization/exposure to both mouse and cockroach was associated with worse asthma in an inner-city community in Baltimore exposed to high levels of both allergens. However, mouse allergen appeared to be more strongly and consistently associated with poor asthma outcomes than cockroach allergen [16,17]. …”
Section: Cockroach Allergy and Inner-city Asthmamentioning
confidence: 99%